2005
DOI: 10.1039/b418658n
|View full text |Cite
|
Sign up to set email alerts
|

Scattering spherical voids in nanocrystalline TiO2? enhancement of efficiency in dye-sensitized solar cells

Abstract: Spherical voids as light scattering centers in nanocrystalline TiO2 films were realized with polystyrene particles of diameter 400 nm, thus enhancing the photovoltaic performance by 25% on large areas, as well as providing an indication that these films can be used with electrolytes of higher viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
218
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(228 citation statements)
references
References 11 publications
10
218
0
Order By: Relevance
“…4d). Apparently, the most complicated TNW-NS-NR architectures with multi-scale nature and interconnected network enable prominent optical confinement via multiple light reflections within the arrays and also are able to scatter the incident light of different wavelengths in the range of visible light 41,42 . This is conducive to extend the distance for light to travel within the photoelectrode, to induce more effective photon capturing in the visible region and thus resulting in an enhancement of light utilization efficiency 43 .…”
Section: Resultsmentioning
confidence: 99%
“…4d). Apparently, the most complicated TNW-NS-NR architectures with multi-scale nature and interconnected network enable prominent optical confinement via multiple light reflections within the arrays and also are able to scatter the incident light of different wavelengths in the range of visible light 41,42 . This is conducive to extend the distance for light to travel within the photoelectrode, to induce more effective photon capturing in the visible region and thus resulting in an enhancement of light utilization efficiency 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Hore et al 14) recently showed that spherical voids in nanocrystalline TiO 2 films can be more efficient in lightscattering centers than solid-scattering centers. Use of hollow scattering centers can provide efficient paths for electrolyte penetration into the electrode film and result in an enhancement of photovoltaic performance by 25 %.…”
Section: 13)mentioning
confidence: 99%
“…This implies a very effective enhancement of the light collected into the cell, but also means that the DSC remains opaque. Nowadays, the scattering layers (Hore et al, 2006;Arakawa et al, 2006), centers (Hore et al, 2005) and superstructures (Chen et al, 2009;Q. F. Zhang et al, 2008) are well known and routinely used (Graetzel, 2005).…”
Section: Photon Managementmentioning
confidence: 99%